Gambaran Identitas Virtual: Studi Kasus Gender Swap dan Seksualitas pada Pemain Original Character Role-player - Raden Ayu Vissy Mega Ryadi; Rahkman Ardi (Universitas Airlangga, 2023)
This study explores virtual identities, specifically gender swapping and sexuality, among Twitter’s original character role-players. Internet anonymity enables freedom of expression. The research focuses on how individuals adopt different gender identities and engage with both genders virtually. Using qualitative intrinsic case study method, this study outlines motivations, experiences, and impacts of gender swapping and sexuality from dramaturgy and symbolic interactionism perspective. Findings reveal that female participants who engage in gender swapping feel liberated from gender norms and construct stronger identity as dominant males. They prefer same-sex relationships based on fujoshi preferences but often avoid commitments. Virtual identity influenced by relationships and communities, by adeptly managing information to maintain specific impressions. The research’s implications uncover increased knowledge and self-expression that is difficult in real life, also highlights negative effects on mental health. This research provides a deeper understanding of the complexities of virtual identity and its influence on individuals' real lives.